P1-S4.17 Interactive demonstration of a model to calculate costs and cost effectiveness of different strategies for chlamydia screening and partner notification. (10th July 2011) - Turner, K; Adams, E; Grant, A; Macleod, J; Bell, G; Clarke, J; Horner, P
Abstract : Background: We have developed a model to calculate costs and cost effectiveness of different intervention strategies for chlamydia screening, which can be used by commissioners to evaluate and plan their local service provision. The model and an analysis of national data have been recently published in BMJ. Increasingly, financial constraints will mean that tools such as ours will be vital to provide value for money in healthcare. Method: We will give a live demonstration of our spreadsheet model using the example from our recent study. We invite delegates to input their own data in real time to a laptop for comparison and testing against the national and international picture. We plan to promote this before the meeting. Main outcome measures: Cost effectiveness of screening (as cost per individual tested, cost per positive diagnosis, total cost of screening, number screened, number infected, sex ratio of those tested and treated). We will show how to compare current programmes with a planned change eg, in screening coverage or partner notification efficacy. Results: In 2008−2009 screening was estimated to cost £46.3 m and £506 per infection treated. The model results suggest that increasing male screening coverage from 8% to 24% (to match female coverage) would cost an extra £22.9 m and increase the cost per infection treated to £528. Increasing partner notification efficacy from 0.4 to 0.8 partners per index case would cost an extra £3.3 m and reduce the cost per infection diagnosed to £449. Conclusions: The results are broadly representative of the national picture, but further evaluation of the cost effectiveness of partner notification and screening is urgently needed. We encourage practitioners who want to test this tool in their own setting to contact us (katy.turner@bristol.ac.uk ). BMJ 2011; 342:c7250 10.1136/bmj.c7250 .